Factors associated with the practice of early complementary feeding and its impact on the nutritional status of infants aged 7 to 23 months - Rika Nurhasanah; Achmad Fauzi; Indria Astuti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Proper complementary feeding plays a crucial role in influencing an infant's nutritional status. Key factors to consider when introducing complementary foods include the starting age, the consistency and texture of the food, the portion size, and the frequency of feeding. Purpose: To identify factors related to the practice of early complementary feeding and their impact on the nutritional status of infants aged 7 to 23 months. Method: A quantitative analytical research with a cross sectional design. Respondent were selected using purposive sampling and the Slovin formula, resulting in 51 respondent from Sipayung Village. Univariate statistical analysis was conducted, including chi square test. Results: The chi-square test revealed a significant relationship between nutritional status and factors such as the age of feeding onset (p=0.015), consistency of delivery (p=0.006), portion size (p=0.000), and feeding frequency (p=0.000). In the